The Relationship of Social Support and Resilience Psychological Well-Being on Student Survivors of Covid-19 - Mic Finanto Ario Bangun; Anneke Putri Pratiwi (PT Publikasiku Academic Solution, 2023)
Covid-19 survivor students who have experienced this will certainly be an unforgettable experience where everything is completely limited in terms of communication and social interaction, coupled with the labeling of 'Covid-19 sufferers' and the emergence of feelings of anxiety and thoughts. Other negatives add to their own problems for survivors. During the healing process, mental disorders arise, such as anxiety, stress, and self-acceptance as a survivor, which affects the individual's psychological condition. Coupled with the social changes during the pandemic, it also adds to psychological problems that will affect the psychological well-being of individuals. Basically, psychological well-being is a feeling that you can control yourself. The condition of a person's psychological well-being also depends on the surrounding environment, one of the factors is social support. This is obtained if a person's high social support and resilience will affect the individual's psychological well-being, especially for students who have survived Covid-19. This study aims to determine whether there is a relationship between Social Support and Resilience to Psychological Well-Being in COVID-19 Survivors. This study uses quantitative methods with correlation techniques, namely multiple correlation test techniques involving as many as 110 students of the Faculty of Psychology at the University Bhayangkara Jakarta Raya. The relationship has a significant positive direction with a strength that is considered strong. And it can be said that the higher the social support and resilience, the higher the level of psychological well-being in student survivors of Covid-19. Vice versa, the lower the social support and resilience, the lower the level of psychological well-being